Cross-site collaboration on infection prevention and control research - room for improvement?: A 7-year comparative study in five European countries - Eichel, Vanessa; Brühwasser, Christina; Castro-Sánchez, Enrique; Birgand, Gabriel; Bathoorn, Erik; Salm, Florian; Mutters, Nico T. (Antimicrobial resistance and infection control, 2022)
The spread of SARS-CoV-2, multidrug-resistant organisms and other healthcare-associated pathogens represents supra-regional challenges for infection prevention and control (IPC) specialists in every European country. To tackle these problems, cross-site research collaboration of IPC specialists is very important. This study assesses the extent and quality of national research collaborations of IPC departments of university hospitals located in Austria, England, France, Germany, and the Netherlands, identifies network gaps, and provides potential solutions.
Gesehen am 27.01.2023